One little lie - Coble, Colleen (Coble, Colleen. Pelican Harbor series., 2020)
"Jane Hardy is appointed interim sheriff in Pelican Harbor, Alabama, after her father retires, but there's no time for an adjustment period. When her father is arrested for theft and then implicated in a recent murder, Jane quickly realizes she's facing someone out to destroy the only family she has. After escaping with her father from a cult fifteen years ago, Jane has searched relentlessly for her mother<U+2014>who refused to leave<U+2014>ever since. Could someone from that horrible past have found them? Reid Bechtol is well-known for his documentaries, and his latest project involves covering Jane's career. Jane has little interest in the attention, but the committee who appointed her loves the idea of the publicity. Jane finds herself depending on Reid's calm manner as he follows her around filming, and they begin working together to clear her father. But Reid has his own secrets from the past, and the gulf between them may be impossible to cross<U+2014>especially once her father<U+2019>s lie catches up with him."--